The Influence of Digital Educational Comic Media on the Reading Comprehension Ability of Grade V Students in MIN 6 Medan City - Syazwina Dinda Damara Rais; Riris Nurkholidah Rambe (Lembaga Bale Literasi, 2026)
This study aims to determine the effect of using Digital Educational Comics media on the reading comprehension skills of fifth-grade students at MIN 6 Medan City. The study employed a quantitative approach using a quasi-experimental design. The research subjects consisted of 54 students divided into an experimental group and a control group, with 27 students in each group. Data were collected through pre-tests and post-tests measuring students' reading comprehension skills. Data analysis was conducted using the Wilcoxon Signed Rank Test because the data did not meet the assumption of normality. The findings revealed that the use of Digital Educational Comics media significantly improved students' reading comprehension skills. The Wilcoxon test results showed a p-value of 0.000 (< 0.05), indicating a significant difference between the pre-test and post-test scores of students in the experimental group. The integration of visual and textual elements in Digital Educational Comics facilitated students' understanding of reading materials, making the learning process more interactive, engaging, and effective. Therefore, Digital Educational Comics can be considered an innovative learning medium to enhance reading comprehension skills among elementary school students.